2015
DOI: 10.1021/ie504772w
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of TiO2-Based Photooxidation of Volatile Organic Compounds: Designing, Coating, and Regenerating Catalyst

Abstract: A TiO 2 -based photocatalytic oxidation study of volatile organic compounds (VOCs: benzene, toluene, ethylbenzene, and xylenes) requiring close monitoring of the catalyst coating, its deactivation, and regeneration was undertaken. For all experiments, the effectiveness of sol−gel coating of nanosized TiO 2 particles (on a glass cylindrical reactor) in terms of the surface morphology, film thickness, and band-gap energy was ensured for obtaining a consistent reactor performance. The estimated VOC degradation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Volatile organic compounds (VOCs), as a kind of toxic substance in air, could pose serious damage to human health [1,2]. As one of typical VOCs, toluene is utilized as an organic solvent in adhesives and paints in the past few years and is likely to be emitted from building material to indoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs), as a kind of toxic substance in air, could pose serious damage to human health [1,2]. As one of typical VOCs, toluene is utilized as an organic solvent in adhesives and paints in the past few years and is likely to be emitted from building material to indoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the capability of photocatalytic materials in VOC destruction is often used for testing their efficiency as photocatalysts. Of the model VOCs pollutants, photocatalytic materials are most frequently tested for their ability to destruct acetone [1][2][3][4][5], formaldehyde [6], methanol [1,7], benzene [5,8], phenol [9,10] and toluene [5,9,11,12]. Of the known photocatalytic materials, titanium dioxide, or titania, in anatase form is typically the photocatalyst of choice for various environmental remediation processes, due to its low cost, chemical stability and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous photocatalysis is regarded as an ideal technology for solving the urgent energy and environmental issues, [11][12][13] especially in removing various gaseous pollutants at ambient pressure and temperature. 14,15 Previous studies have also indicated CH 4 molecules can be activated and subsequently oxidized via TiO 2 photocatalytic technology, 16,17 however, the efficiency of CH 4 photo-oxidation remains notoriously low. Adsorption and photoreaction are two successively key steps, which are generally interactional during the heterogeneous photocatalytic process.…”
Section: Introductionmentioning
confidence: 99%